Ethical Issues in Private Practice: A Phenomenological Investigation of Music Therapy Business Owners. (2nd March 2021) - Wilhelm, Kyle; Wilhelm, Lindsey
Abstract: As a music therapy private practice is both a business and a healthcare service, it should adhere to ethical standards from both disciplines. However, this topic has rarely been examined in the music therapy literature. The purpose of this phenomenological study was to explore ethical dilemmas experienced by music therapy business owners (MTBOs) in their private practice and how MTBOs avoid or address ethical dilemmas. Utilizing convenience and snowball sampling techniques, 21 MTBOs in the United States were interviewed using semi-structured interviews. To answer the two areas of inquiry, we identified three themes and 12 subthemes: (1) Ethical issues related to client welfare, (2) Ethical issues related to business relationships and operation, and (3) Strategies to address or avoid ethical dilemmas. MTBOs also shared how they ensure ethical behavior in themselves, with their employees or independent contractors, and when interacting with professionals outside the private practice. These findings provide a better understanding of MTBOs' lived experiences of ethics in their private practice and may benefit other music therapists who are in private practice or are wanting to go into private practice. Limitations and recommendations for further research are provided.